(untitled) (Nepal Medical College Journal, 2025)
Acute pesticide poisoning is a significant public health concern in developing countries, including Nepal, where agriculture remains a major occupation. The easy accessibility and improper handling of pesticides contribute to both intentional and accidental poisonings. This study is intended to evaluate the clinical characteristics, treatment outcomes, and patterns of acute pesticide poisoning among patients presenting to the emergency department of a tertiary care center in Eastern Nepal. A descriptive cross-sectional study was done in the emergency department of a tertiary care center in Eastern Nepal during a defined study period. Data were collected using a structured proforma, including demographic details, type and route of poisoning, clinical presentation, management provided, and patient outcomes. Descriptive statistical techniques were employed to interpret the data. A total of 688 cases of acute pesticide poisoning were included. The majority of patients were young adults aged 15–30 years, with a higher prevalence among females. Organophosphates were the most commonly implicated agents (44.2%) followed by rodenticides and organochlorine. Most cases were intentional ingestion. Common symptoms included vomiting, altered sensorium, and respiratory distress. Supportive management, along with atropine and pralidoxime for organophosphate poisoning, was provided. The majority recovered with timely intervention, though 19.6% experienced complications and 6.3% mortality was recorded. Acute pesticide poisoning remains a prevalent and preventable health issue in Eastern Nepal, particularly among young individuals. Early recognition and prompt management are essential to improving outcomes. Strengthening regulation on pesticide sales, public awareness, and mental health interventions are critical to reducing the incidence of such poisonings.